The expected role of individuals in the transition to net zero: policies and pathways facilitating an active role - Fawcett, T (European Council for an Energy Efficient Economy, 2022)
Responding to the climate emergency is widely recognised as a priority at all levels of government – from cities up to the EU. However, what this means for individuals is under debate: are individuals expected to be active citizens co-creating the transition, disengaged recipients of net zero policies, or something in between? This exploratory paper first summarises the debate about whether individual change is a distraction from demanding system change. It concludes that individual change is inextricably linked with system change. Individuals can have roles in the energy system and transition beyond that of the economically-rational consumer. Indeed, characterisation of current energy efficiency policy shows that a variety of conceptualisations of individuals are already present in European and national policy. Moving beyond efficiency, new ways of engaging individuals - personal carbon allowances, carbon footprints and energy sufficiency - are considered. The most radical is energy sufficiency which encompasses a very broad understanding of individuals, their needs and wants, and their relationship to the natural environment. Looking at various net zero scenarios shows increased individual engagement will be required to reduce / remove reliance on highly uncertain carbon dioxide removal technologies. This paper builds a picture of how the individual is seen in energy transition research and practice. There are differing expectations according to context, and who is doing the expecting. The paper argues that there are reasons in principle and practice to prefer engaged citizens, and points to policies and pathways which facilitate this active role. Policies which combine multiple levers of change - economic, social and psychological - and/or which move beyond efficiency to sufficiency, will be important in the energy transition.